Internal Control in the University Governance: A Case Study of the Malaysia University of Sabah - Asmady Idris; Mohd Shaukhi Mohd Radzi (2009)
Every organization, including the institution of higher learning, has its own vision and objectives to be achieved. However, in running an organization, management cannot avoid unwarranted surprises. Therefore, in reducing these unwanted risks, an organization may rely upon its internal control system. This system is able to help an organization to realize its desired goals and objectives more efficiently. The vision of UMS (Malaysia University of Sabah) is to become an innovative university of the global standing. In realizing this vision, all the academic members of UMS must strive hard to help the university. Apart from strengthening the standard of the quality of academic and research, the recruitment of the academic staff is also crucial. The recruitment of new academic staff must be properly done according to the rules and procedures. The role of internal control must be emphasized in this process. By sharing our experience as the management team, we manage to discuss the process of staff recruitment based on the internal control system in the School of Social Sciences UMS. We found that the internal control is important in choosing the right academic staff for a school or faculty. Five components of internal control must be obeyed in reducing unwarranted risks in the staff recruitment process. We think that the university top management also has given their solid support for the school.